Tradisi Mangongkal Holi Batak Toba: Eksplorasi Kesesuaian dengan Perspektif Alkitabiah 2 Samuel 21:12-14 - Purba, Edward; Hutagalung, Stimson (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2024)
This study compares the Toba Batak Mangongkal Holi Tradition to 2 Samuel 21:12-14's Biblical perspective. To understand the Toba Batak culture's Mangongkal Holi ceremony challenges, this study uses a qualitative descriptive approach. Researchers actively participate in the whole study process, from problem identification to findings, in this research approach. Purposive selection was used to select informants. Data was collected by interviewing respondents, examining the GMAHK community's views of Toba Batak Culture and Mangongkal Holi, and preserving historical data. A qualitative approach was used to accurately depict current situations in data analysis. Credibility tests verify data, while data processing involves interpreting and analysing data to determine its significance. The research shows how local rituals and traditions can include religious ideals like reverence for ancestors without spiritualism or prayer. Despite differences in practice, culture and religion can coexist and provide a moral foundation for society. This study concludes that intercultural discourse and religious understanding maintain social and spiritual balance in heterogeneous communities.